Evaluation of values, beliefs and norms of high school students on the conservation of biodiversity - Bilir, Ahmet; Özbaş, Serap (Journal of Turkish Science Education, 2017)
This research evaluates the values, beliefs and norms on conserving biodiversity amongst Turkish Cypriot high school students and the results are compared according to gender and class year individually. The data was collected from 506 students via a value-belief-norm questionnaire. According to the results of this questionnaire, it is observed that the Turkish Cypriot high school students pay more attention towards the “self-administration” value, believe that their responsibility towards protecting the local and global biodiversity is more than their perception of talent to manage it and their personal norms regarding the conservation of biodiversity is very similar to each other. Furthermore, it can be concluded that gender and grade does have an effect on the values, beliefs and norms on preserving biodiversity.